1986
DOI: 10.1161/01.cir.74.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracardiac blood flow velocities and right and left ventricular stroke volumes with gestational age in the normal human fetus: a prospective Doppler echocardiographic study.

Abstract: We used Doppler echocardiography to quantitate the changes in intracardiac blood flow velocities and right and left ventricular stroke volumes in 80 normal human fetuses from 19 to 40 weeks gestation. Blood flow velocity spectra across the aortic, pulmonary, tricuspid, and mitral valves were digitized to obtain peak velocities (m/sec) and flow velocity integrals. Aortic and pulmonary diameters were measured at valve level from two-dimensional echocardiographic images and cross-sectional area was calculated ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
2
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(146 citation statements)
references
References 39 publications
(3 reference statements)
14
120
2
10
Order By: Relevance
“…The nature of the fetal pulmonary venous flow waveform pattern suggests positive pressures towards the left atrium thorough the cardiac cycle. The pattern of pulmonary venous flow velocity, may be altered in many physiologic and pathologic situations, such as heart rate 24 , cardiac output 25 , absolute pulmonary flow 26 , left atrial pressure 22 and function, mitral valve function, left ventricle pressure and function 22 . Talbert and Johnson 27 suggested that the change of shape of the pulmonary venous flow waveform reflects the changes in the pressure waveform of the left atrium and represent the atrial pressure response to both intracardiac and systemic vascular status.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the fetal pulmonary venous flow waveform pattern suggests positive pressures towards the left atrium thorough the cardiac cycle. The pattern of pulmonary venous flow velocity, may be altered in many physiologic and pathologic situations, such as heart rate 24 , cardiac output 25 , absolute pulmonary flow 26 , left atrial pressure 22 and function, mitral valve function, left ventricle pressure and function 22 . Talbert and Johnson 27 suggested that the change of shape of the pulmonary venous flow waveform reflects the changes in the pressure waveform of the left atrium and represent the atrial pressure response to both intracardiac and systemic vascular status.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques of fetal cardiac imaging and measurements have been reported elsewhere [7][8][9][10][11][12][13][14] . All parameters measured were re-analyzed off-line by one of the authors (E.T.J).…”
Section: Ultrasound Recordingsmentioning
confidence: 99%
“…However, the reported ratio of right to left cardiac output ranges from 1.0 to 1.5. [2][3][4][5][6][7] The very few studies that have focused on blood flow through the ductus arteriosus and through the pulmonary circuit in the human fetus have given conflicting results. 4,7 For these reasons, a prospective cross-sectional study that used high-resolution ultrasound equipment, including color Doppler imaging, was performed to establish gestational age-specific reference ranges for left and right cardiac output, combined cardiac output, and volume of blood flow across the ductus arteriosus.…”
mentioning
confidence: 99%